114k views
1 vote
Suppose a country's population at any time t grows in accordance with the rule dP dt = kP + I where P denotes the population at any time t, k is a positive constant reflecting the natural growth rate of the population, and I is a constant giving the (constant) rate of immigration into the country. If the total population of the country at time t = 0 is P0, find an expression for the population at any time t.

1 Answer

0 votes

Answer:


\mathbf{P =\bigg (P_o +( I)/(k) \bigg)e^(kt)- (I)/(k)}

Explanation:

Given that:

A country population at any given time (t) is:


(dP)/(dt)= kP+I

where;

P = population at any time t

k = positive constant

I = constant rate of immigration into the country.

Using the method of separation of the variable;


(dP)/(kP+1)= dt

Taking integration on both sides:


\int (dP)/(kP+I)= \int \ dt


(1)/(k) log (kP + I) = t+c_1 \ \ \ here: c_1 = constant \ of \ integration


log (kP + I) =k t+kc_1

By applying the exponential on both sides;


e^(log (kP + I) )=e^(k t+kc_1 )


KP+I = e^(kt) *e^(kc_1)

Assume
e^(kc_1 )= C

Then:


kP + I = Ce^(kt)


kP = Ce^(kt)-I


P =( Ce^(kt)-I)/(k) \ \ \---- Let \ that \ be \ equation \ (1)

When time t = 0, The Total population of the country is also
P_o


P_o = (Ce^(0(t)) -I)/(k)


P_o = (Ce^(0) -I)/(k)


P_o = (C-I)/(k)

C - I = kP₀

C = kP₀ + I

Substituting the value of C back into equation(1), we have:


P =( (kP_o+1)e^(kt)-I)/(k)


P =( (kP_o+1)e^(kt))/(k) - (I)/(k)


\mathbf{P =\bigg (P_o +( I)/(k) \bigg)e^(kt)- (I)/(k)}

User Lorita
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.